Respuesta :
Answer:
1.62 × 10⁻³ M s⁻¹
Explanation:
Let's consider the following reaction.
2 NO₂ + F₂ = 2 NO₂F
The generic rate law is:
rate = k × [NO₂]ᵃ × [F₂]ᵇ
where,
- rate: reaction rate
- k: rate constant
- a and b: reaction orders with respect to the reactants
The reaction is first order in NO₂ and first order in F₂ and the rate constant is k = 1.58 × 10⁻⁴ M⁻¹ s⁻¹.
The rate law is:
rate = 1.58 × 10⁻⁴ M⁻¹ s⁻¹ × [NO₂] × [F₂]
When [NO₂] = 2.84 M and [F₂] = 3.60 M, the reaction rate is:
rate = 1.58 × 10⁻⁴ M⁻¹ s⁻¹ × 2.84 M × 3.60 M
rate = 1.62 × 10⁻³ M s⁻¹
Answer:
a) The rate of reaction is [tex]Rate=k[NO_{2}] [F_{2} ][/tex]
b) The rate of reaction is 0.00161 Ms⁻¹
Explanation:
a) The reaction is:
2NO₂ + F₂ = 2NO₂F
The rate of the reaction is equal:
[tex]Rate=k[NO_{2}]^{m} [F_{2} ]^{n}[/tex]
The rate of reaction (m) respect to NO₂ is 1 and the rate of reaction (n) respect to F₂ (n) is 1, thus the rate is:
[tex]Rate=k[NO_{2}] [F_{2} ][/tex]
b) Using the rate of part a) and
k = 1.58x10⁻⁴M⁻¹s⁻¹
[NO₂] = 2.84 M
[F₂] = 3.6 M
[tex]Rate=1.58x10^{-4} *(2.84)*(3.6)=0.00161M s^{-1}[/tex]